(untitled) (Bangladesh Journal of Medical Science, 2013)
Background: Diarrhoea is a leading cause of morbidity and mortality in developing countries. This study observed the influences of nutritional status and age on the outcome of severe diarrhoea in adult male patients. Methods and materials: Data were obtained through interview by arranged questionnaire. It is a prospective longitudinal study, where one group of patient was well nourished and other group was malnourished. Results: Significant differences were found in all study factors between malnourished and well nourished diarrhoea patients. Patients with poor nutritional status had low body weight and muscle mass index than well nourished patients. The stool volume was higher in malnourished patients than well nourished patient. In addition mean duration of diarrhoea for malnourished patients was higher than well nourished patients until discharge from hospital. Conclusion: Therefore, the diarrhoea of malnourished and low socioeconomic status of adult patients is more severe, and the incidence of this disease can be reduced by growing awareness as well as improve nutritional and socioeconomic status of those patient groups. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 250-255 DOI: http://dx.doi.org/10.3329/bjms.v12i3.15406